Energy-Efficient Adaptive Routing and Context-Aware Lifetime Maximization in Wireless Sensor Networks - Shaohua Wan (International Journal of Distributed Sensor Networks)
We design and implement a Bezier-based multipath routing algorithm that allows a given source node to send samples of data to a given sink node in large scale sensor networks. Multipath routing can distribute the energy load onto the multiple routes and thus increase the lifetime and quality of the network. It is important to stress the fact that evenly regulating the routing task among the more nodes of the network can also protect a node from failure considering that a node with heavy duty is likely to deplete its power quickly. On the contrary, all the traffic would be shipped along the shortest path routing, corresponding to the heavily congested path case, which in turn leads to overload of the nodes along the optimal routes between the sink and source pair and finally shortens the lifetime of the network. Also, multipath routing can increase end-to-end throughput and provide load balancing. Our view is that minimizing energy consumption while meeting acceptable latency for applications can lead to significant power savings. Our simulation results demonstrate that Bezier-based multipath routing approach significantly outperforms previous SWEEP, Tributaries and Deltas, and the shortest path approaches in terms of lifetime and latency.